2014
DOI: 10.1016/j.toxlet.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of human nuclear hormone receptor activity and cytotoxicity of the flame retardant mixture FM 550 and its triarylphosphate and brominated components

Abstract: Firemaster® 550 (FM 550) is a mixture of brominated and triarylphosphate flame retardants used in polyurethane foam-based products. The primary components are also used in numerous other applications and are thus common household and industrial contaminants. Our previous animal studies suggested that FM 550 exposure may alter metabolism and cause weight gain. Employing human nuclear receptor (NR) luciferase reporter assays, the goal of this study was to evaluate the agonist actions of FM 550 and its constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 32 publications
(50 reference statements)
4
75
0
1
Order By: Relevance
“…While limited to only one study, this perinatal exposure suggests that exposure to FM 550 can alter adipogenic and developmental pathways. As a follow-up to this study, researchers also investigated the effects of FM 550 and its individual components on nuclear receptor activation [77*] and adipogenic and osteogenic pathways in cell culture [78*]. Combined results from these studies suggest that FM 550, and particularly TPP, may be eliciting an obesogenic phenotype due to activation of the nuclear receptor PPARγ and upregulation of adipogenesis, which may occur at the expense of osteogenesis.…”
Section: Endocrine Related Effects Of Frsmentioning
confidence: 99%
“…While limited to only one study, this perinatal exposure suggests that exposure to FM 550 can alter adipogenic and developmental pathways. As a follow-up to this study, researchers also investigated the effects of FM 550 and its individual components on nuclear receptor activation [77*] and adipogenic and osteogenic pathways in cell culture [78*]. Combined results from these studies suggest that FM 550, and particularly TPP, may be eliciting an obesogenic phenotype due to activation of the nuclear receptor PPARγ and upregulation of adipogenesis, which may occur at the expense of osteogenesis.…”
Section: Endocrine Related Effects Of Frsmentioning
confidence: 99%
“…Furthermore, the human aryl hydrocarbon receptor (AhR), human constitutively active receptor and human pregnane X receptor (PXR) pathways were found to be affected by OPEs (Gerlach et al, 2014;Honkakoski et al, 2004). The results of two recent studies suggested that some of these OPE compounds could exert their toxicity via the activation of the peroxisome proliferator-activated receptor (PPARγ) pathway (Belcher et al, 2014;Fang et al, 2015). Furthermore, Kojima et al (2013) evaluated the effects of OPEs against eight human nuclear receptor pathways and found that four of these pathways were affected by the OPEs:ER agonistic activity, androgen receptor antagonistic activity, glucocorticoid receptor antagonistic activity and PXR agonistic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Belcher and coworkers studied the structural similarities between TPP and triphenyl tin (TPT) chloride, whose structures are given in Figure 1. TPT chloride is a favorable ligand for peroxisome proliferator-activated receptor gamma (PPARγ) from the endocrine system, as well as a metabolic disruptor (12), and thus they speculated that, in a way similar to organotin chemicals, TPP may play a role in the obesogenic effects caused by FM 550 exposure. Pillai and coworkers confirmed that TPP increased human PPARγ transcriptional activity, and thus through environmental exposure, it may potentially lead to obesity and osteoporosis in humans (13).…”
Section: Introductionmentioning
confidence: 99%